Pengaruh Net Working Capital dan Ukuran Perusahaan terhadap Cash Holding pada Perusahaan Sektor Consumer Cyclicals di Bursa Efek Indonesia - Siti Mariani; Muhammad Iqbal Pribadi; Rahman Anshari (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to examine the influence of net working capital and company size on cash holding in the consumer cyclicals sector listed on the Indonesia Stock Exchange (IDX). The type of research used is a quantitative approach using panel data regression analysis techniques. The population in this study is 166 companies in the consumer cyclicals sector listed on the IDX, then for sampling using the purposive sampling method. There were 107 samples of companies with an observation period of 3 years 2021-2023 (321 data). The type of data studied is secondary data. The data of this research was obtained from financial statements published on the official website of each company and the official website of the IDX. The results of the study show that partially net working capital has a positive and significant effect on cash holding, then company size has a negative and significant effect on cash holding.